Radar discrimination of small airborne targets through kinematic features and machine learning - Doumard, Timothée; Gañán Riesco, Fabio; Petrunin, Ivan; Panagiotakopoulos, Dimitrios; Bennett, Cameron; Harman, Stephen (IEEE, 2022)
This work studies binary classification problem for small airborne targets (drones vs other) by means of their trajectory analysis. For this purpose a set of the kinematic features extracted from drone trajectories using radar detections with a classification scheme that utilises Random Forests is proposed. The development is based on experimental data acquired from the Holographic radar from Aveillant Ltd. An approach for real-time classification is proposed, where an adaptive sliding window procedure is employed to make predictions over time from trajectories. Several models utilising different kinematic features (angle, slope, velocity, and their combination) are studied. The best model achieves an accuracy of more than 95%. In addition, fundamental issues with imbalanced datasets in the context of this topic are raised and illustrated using the collected data.
Keywords: Drone; classification; trajectory; motion; machine learning